Annual plant reviews, Volume 14:Plant Pigments and their Manipulation - Davies, Kevin M (Blackwell, 2012)
Plant pigments represent an active field of research that impacts fundamental studies of plant function and gene expression, agriculture, the processing of foods and human health. This book reviews major plant pigment groups, considering the underlying biology, genetic manipulation, and applications of plant pigments within agriculture.